Dampak Globalisasi terhadap Pendidikan Multikultural dalam Pembelajaran PKn - Liandy, Septian (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This study examines the impact of globalization on multicultural education in Civic Education (PKn) learning at elementary schools, aiming to analyze its effects and develop adaptive teaching strategies. Using a qualitative library research method, the study focuses on academic literature published within the last five years (2019–2024), with subjects including theories of globalization and multicultural education, while the object is PKn learning in elementary schools. Data were collected through systematic literature review and analyzed using content analysis to identify patterns and gaps. The results reveal that globalization has led to greater exposure to foreign cultures among students, overshadowing local values, while also highlighting the lack of teacher preparedness in integrating multicultural approaches. The study concludes by recommending curriculum updates, teacher training, and technology-based learning materials to strengthen multicultural values in PKn.